Removal of Cu(II) from Water Environment Using Lignocellulose/Montmorillonite Nanocomposite-An Industrial Waste Adsorbent - Zhang1, Xiaotao; Wang2, Ximing (Asian Journal of Chemistry, 2014)
The lignocellulose/montmorillonite nanocomposite was taken as adsorbent to investigate the adsorption and desorption properties of Cu(II) in copper-contained wastewater, which was synthesized by the chemical intercalation process of lignocellulose and montmorillonite. The affecting parameters on the Cu(II) removal rate by changing initial concentration of Cu(II), solution pH, adsorption temperature and adsorption time were studied. The equilibrium adsorption capacity could reach 322.56 mg g-1 under the optimal condition, i.e., 0.03 mol L-1 initial concentration of Cu(II) ion, 4.9 is the solution pH, 50 ºC is the adsorption temperature and 60 min is the adsorption time. The pseudo-second order kinetic model can well describe the whole adsorption process and the isotherm adsorption equilibrium conformed to the Langmuir model. The adsorption mechanism of lignocellulose/montmorillonite was discussed in combination with the results of SEM and FTIR. And then lignocellulose/montmorillonite could be easily eluted by HNO3, the effects of HNO3 concentration, desorption temperature and desorption time on desorption capacity of lignocellulose/montmorillonite were tested. The results showed that HNO3 concentration 0.1 mol L-1, desorption temperature 40 ºC and desorption time 0.5 h, the satisfactory effect of desorption capacity was 283.15 mg g-1. The adsorption/desorption experiment displayed that the adsorption capacity of lignocellulose/montmorillonite was ideal for four cycles, so lignocellulose/montmorillonite is confirmed a high efficient adsorbent for recycling.